Thaw Consolidation, Thaw Settlement, and Hydromechanical Properties of Thawed Permafrost from the Mackenzie Valley, Canada ... - Nazeri, Arian; Picard, Zakary; Janghorban Laricheh, Vahid; Valois, Anthony; Dumais, Simon (Borealis, 2025)
This dataset contains geotechnical experimental test results on permafrost samples collected from the Mackenzie Valley, Canada. These samples were obtained during investigations conducted by the Northern Engineering Service Company Limited in the 1970s for the proposed Arctic Gas Pipeline Route project. It includes the geotechnical characterization and index properties of the soil samples, along with their descriptions. Laboratory test results for thaw consolidation, thaw settlement, and thawed permeability of selected samples are also provided. The data is presented as originally reported in the Northern Engineering Services Company Limited's reports. ...